Biting the hand that feeds: Metabolic determinants of cell fate during infection - Fraschilla, Isabella; Evavold, Charles L. (Frontiers in Immunology, 2022)
Metabolic shifts can occur in cells of the innate immune system in response to microbial infection. Whether these metabolic shifts benefit host defense and propagation of an immune response appears to be context dependent. In an arms race, host-adapted microbes and mammalian cells vie for control of biosynthetic machinery, organelles, and metabolites. Herein, we discuss the intersection of host metabolism and cell-intrinsic immunity with implications for cell fate during infection. Sensation of microbial ligands in isolation results in host metabolic shifts that imbues normal innate immune function, such as cytokine secretion. However, living microbes have an arsenal of effectors and strategies to subvert cell-intrinsic immune responses by manipulating host metabolism. Consequently, host metabolism is monitored as an indicator of invasion or manipulation by a pathogen, primarily through the actions of guard proteins and inflammasome pathways. In this review, we frame initiation of cell-intrinsic immunity in the context of host metabolism to include a physiologic “Goldilocks zone” of allowable shifts with guard circuits monitoring wide perturbations away from this zone for the initiation of innate immune responses. Through comparison of studies with purified microbial ligands, dead microbes, and live pathogens we may begin to understand how shifts in metabolism determine the outcome of host-pathogen interactions.